Seasonal variability of phytoplankton community response to thermal discharge from nuclear power plant in temperate coastal area. (1st February 2023) - Zhang, Jingjing; Wang, Yibin; Ottmann, Daniel; Cao, Peng; Yang, Jisong; Yu, Junbao; Lv, Zhenbo
Abstract: Nuclear power plants (NPPs) developed rapidly worldwide in the last half-century and have become one of the most important electric power sources. Thermal discharge from NPPs increases the temperature of receiving waters, directly and indirectly affecting phytoplankton community. Seasonal and interannual variation in environmental factors in temperate areas makes it challenging to determine the effects of thermal effluents from NPPs on coastal phytoplankton. Here, a five-year study was performed around a NPP in the western Yellow Sea to determine how thermal effluents affect phytoplankton community during different seasons. A total of 106 phytoplankton species from 7 phyla were identified in 10 biological sites during the 19 cruises, among which diatoms dominated phytoplankton abundance in all seasons. Our results show that increased seawater temperature caused by thermal effluents (1) was not enough to cause a statistically significant effect on phytoplankton abundance composition from autumn through spring, (2) significantly stimulated phytoplankton population growth and changed phytoplankton composition in summer (3) increased the proportion of diatoms and decreased the proportion of dinoflagellate in summer, and (4) increased the abundance and dominance of Skeletonema costatum sensu lato, especially in summer. The findings of this study provide essential information on the ecological impact of thermal effluents from NPPs in temperate coastal areas. Graphical abstract: Image 1 Highlights: Thermal effects on phytoplankton varied greatly between seasons. Thermal discharge significantly promoted phytoplankton growth in summer. Thermal discharge has no significant effect on phytoplankton community from autumn to spring. Thermal discharge reshaped phytoplankton community structure in summer. Release of thermal effluent was closely related to dominant species succession.